Feasibility Assessment of Mangrove in Two Villages on Bengkalis Island for Ecotourism - Aryodamar Muhammad Jati; Nurul Qomar; Defri Yoza (Jurnal Natur Indonesia, 2023)
Mangroves are a unique ecosystem that has an important role both bio-physically and socio-economically. Unfortunately, this ecosystem has suffered damage due to various forms of unwise use. Alternatively, the use of mangroves for ecotourism is often seen as more environmentally friendly and sustainable. On the other hand, some factors limit the success of mangrove ecotourism management. One of the most important factors is the feasibility of the mangrove itself as a capital for ecotourism. This study aims to evaluate the characteristics of mangroves in two villages on Bengkalis Island as ecotourism resources and to analyze their suitability as an ecotourism attraction. Data were collected through direct observation and interviews in Kuala Alam and Pematang Duku Village in Bengkalis District, Bengkalis Regency, Riau Province. The feasibility is analyzed using the Tourism Suitability Index (TSI) based on parameters that have been set by the TSI. The mangroves in Kuala Alam have an average cover thickness of 337 m, with a density of 300 trees/ha, which are composed of nine tree species. Mangroves in Pematang Duku have an average cover thickness of 948 m, with a density of 500 trees/ha, consisting of 14 tree species. The mangrove fauna found in the two villages is generally the same, as with the tidal pattern. The mangroves in Kuala Alam Village achieve a score of 1.75 which means they do not have tourism suitability (TSI<2) while mangroves in Pematang Duku achieve a score of 2.38 which meet the criteria to develop mangrove ecotourism (TSI>2).